Deformation Analysis of Low Rigidity Part Due to Cutting Force of Milling Process for Modular Fixture Design Using Finite Element Method - Sugesti, Putra
Low Rigidity Part is a type of component in aircraft construction. Low Rigidity is designed with thin thickness dimensions so that the weight of the aircraft becomes lighter. The components are derived from prismatic blocks, then carried out with milling process. However, due to the cutting force during the process, Low Rigidity components often rejected because deformation that exceeds the tolerance limit. One of the solution is to create a fixturing system that has a support element to resist deformation and have modular characteristic in order to be more economical. In this study the positioning of the support elements is based on the location of the deformed product that exceeds the tolerance limit. Deformation due to cutting forces can be determined by static analysis, to get the magnitude and direction of the deformation that occurs. For the cutting force itself is obtained by carrying out numerical simulations of the threedimensional finite element method with Smoothed Particle Hydrodynamics. Simulation results can represent the actual cutting force and deflection with a range of error values of 25–40%. The simulation results also show the analysis of the use of support elements with the finite element method in the landing gear case study can reduce product deflection, from 117 ?m to 20 ?m, which means the product can be accepted based on tolerance criteria.